The relationship between coaches' emotional intelligence and basic need satisfaction in athletes. Issue 3 (2nd September 2019) - Watson, Matthew; Kleinert, Jens
ABSTRACT: Scant empirical evidence exists on the importance of coaches' emotional intelligence (EI). This cross-sectional study examined whether coaches' EI is linked to the perception and satisfaction of their athletes' basic psychological needs. Coaches ( n  = 16, male = 68.8%, mean age = 33 ± 11 yrs) and youth athletes ( n  = 171, male = 46.9%, mean age = 15 ± 1.5 yrs) from 16 non-elite German sports teams (basketball n  = 3, football n  = 5, handball n  = 3, and volleyball n  = 5) participated in this research. Coaches' EI, athletes' need satisfaction, and athletes' perceived autonomy support were assessed by self-report questionnaires. Multilevel analyses showed that coaches' EI self-control significantly predicted the accuracy of coaches' perceptions of athletes' competence satisfaction. Furthermore, coaches' EI well-being significantly related to athletes' perceived autonomy support. Findings suggest a partial role of coaches' EI in supporting athletes' need satisfaction.